PERILAKU DISIPLIN SISWA DITINJAU DARI ASPEK PENGENDALIAN DIRI (SELF CONTROL) DAN KETERBUKAAN DIRI (SELF DISCLOSURE) PADA SISWA SMKWONOASRI CARUBAN KABUPATEN MADIUN - Widodo, Bernardus (Widya Warta, 2013)
This research aimsto determine the degree of influence of the self-control and self-disclosure for the establishment of disciplinary behavior model of students at school. The object of this research is the students of SMK PGRI Wonoasri Caruban Madiun of academic year 2011/2012, with131 students as its sampel.The analysis shows that (1) the first minor hypothesis is acceptable, based on the results of hypothesis test with the t value the 2865; t table = 1.658, p = 0.005 (significant) at 5% significance level, (2) the second minor hypothesis is acceptable, based on the results of hypothesis test with the t value = 9267; t table = 1.658, p = 0.000 (significant) at 5% significance level, (3) the major hypothesis indicates that there is a significant influence of self-control and self-disclosure toward disciplinary behavior. The data processing reveals the F value =46,856, at 5% significance level with F table = 2.290. This means that the major hypothesis is acceptable, because F value > F table.The findings of this research provide clear information that internal factors such as self-control and self-disclosure strongly influence the formation of the students’ disciplinary behavior with a contribution = 67.2%. It is very important for teachers as educators, school counselors as wellas for students themselves to consider the influenceof these two factors.